2013
DOI: 10.1016/j.jsv.2013.06.033
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of airfoil instability tonal noise with trailing edge serrations

Abstract: This paper presents an experimental study of the effect of trailing edge serrations on airfoil instability noise. Detailed aeroacoustic measurements are presented of the noise radiated by an NACA-0012 airfoil with trailing edge serrations in a low to moderate speed flow under acoustical free field conditions. The existence of a separated boundary layer near the trailing edge of the airfoil at an angle of attack of 4.2 degree has been experimentally identified by a surface mounted hot-film arrays technique. Hot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 101 publications
(58 citation statements)
references
References 31 publications
(66 reference statements)
2
55
1
Order By: Relevance
“…The currently available approaches can be categorized as passive methods and active methods. The examples of the former one include the application of TE serrations, [10][11][12][13][14][15][16][17] TE brushes, 18,19 porous material, [20][21][22][23][24][25] surface treatments, [26][27][28][29] shape optimization and morphing, 30 etc. The efficiency of the passive methods is limited to a given range of conditions and out of this range they might introduce undesired losses.…”
Section: Nomenclaturementioning
confidence: 99%
“…The currently available approaches can be categorized as passive methods and active methods. The examples of the former one include the application of TE serrations, [10][11][12][13][14][15][16][17] TE brushes, 18,19 porous material, [20][21][22][23][24][25] surface treatments, [26][27][28][29] shape optimization and morphing, 30 etc. The efficiency of the passive methods is limited to a given range of conditions and out of this range they might introduce undesired losses.…”
Section: Nomenclaturementioning
confidence: 99%
“…4a. Several familiar features pertaining to the laminar instability tonal noise are discernible: 1) the existence of velocity scaling laws U 1.5 and U 0.8 for the broadband hump and discrete tones, respectively [13,14]; and 2) the existence of the "ladder" structure. The result indicates that bypass boundary layer transition on the aerofoil surfaces was not triggered due to the low freestream turbulence intensity.…”
Section: A No Grid Case: Low Turbulence Jetmentioning
confidence: 99%
“…They also observed that the sharpness of the sawtooth affected the turbulent length scale and the turbulent intensity in the boundary layer region compared to the baseline case. The effects of serrations on airfoil's laminar flow instabilitiy noise was carried out by Chong and Joseph [28]. They showed that the sawtooth surface can trigger a bypass transition and prevent the boundary layer from becoming separated, subsequently reducing the two-dimensionality and preventing the amplification of the Tollmien-Schlichting waves.…”
Section: Introductionmentioning
confidence: 99%